Modified DRTA (Directed Reading Thinking Activity) Strategy to Enhance Students' Reading Comprehension - Nelvia Kurnia; Benni Satria; Hanifah (Juliet, 2022)
The objective of this research was to boost students' reading comprehension of narrative text by modifying DRTA (Directed Reading Thinking Activity) strategy at X MIPA 3 students of SMA Negeri 1 Bintan Timur. The research design was classroom action research. This study held at two cycles with four meetings in each cycle. The subjects of this research were X MIPA 3 students which made up 36 students. The research instruments applied to gather the data were observation checklist and reading comprehension test. The result showed that students' percentage whose got score ≥ 75 in cycle 1 and cycle 2 were higher than preliminary study. There were 63,88% students in cycle 1 and 88,88% students in cycle 2. It showed that the students' percentage whose got score ≥ 75 improved and meet the criterion of success was 70%. The observation checklist's results also showed that modified DRTA (Directed Reading Thinking Activity) strategy was successful in enhanciing students' classroom participation. The students' participation had been reached 83% in cycle 2. From the result, ≥ 40% students participated in the teaching and learning activities when the strategy was implemented. It could be concluded that the modified DRTA (Directed Reading Thinking Activity) strategy could improve students' reading comprehension and students' participation at X MIPA 3 students of SMA Negeri 1 Bintan Timur.